Blockchain Technology in Fashion Management, Merchandising & SCM: A Comprehensive Literature Review and Conceptual Framework for the Textile Industry in TN - Sadurya, G.; Selvaranee, J. Kavitha (Indian Journal of Information Sources and Services, 2026)
Block Chain Technology (BCT) is a decentralized and immutable digital ledger that records transactions across multiple computers, enabling secure, tamper-proof, and transparent data management in complex networks. This research uniquely investigates the application of BCT in Supply Chain Management (SCM) within the textile industry of Tamil Nadu (TN), a region recognized as the powerhouse of India’s textile sector. The study addresses the research problem of how BCT adoption can revolutionize fashion management and merchandising in TN by enhancing traceability, transparency, and operational efficiency throughout the supply chain. A systematic review of literature from 2019–2024 is conducted, focusing on BCT’s impact on supply chain performance, information transparency, and buyer-supplier relationship in TN’s textile sector. The methodology includes analysing empirical studies and industry reports to test hypotheses regarding BCT’s effect on SCM performance, its role in delivering transparent information for fashion management, and the challenges of adoption in TN’s textile industry. Findings highlight, BCT enables real-time tracking of products from raw materials to final goods, automates processes through smart contracts, and assures product authenticity, significantly improving transparency and trust among all stakeholders. Consumers benefit from the ability to verify product origins and quality, while manufacturers experience enhanced operational efficiency and reduced risk of counterfeiting. However, challenges such as high implementation costs, technological barriers, and the need for industry-wide collaboration remain prevalent obstacles to widespread adoption. This study’s novelty lies in its region-specific, comprehensive evaluation of BCT’s transformative potential and practical challenges within TN’s textile industry, providing actionable insights for future research and industry practice.